2017
DOI: 10.1016/j.nicl.2017.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar degeneration affects cortico-cortical connectivity in motor learning networks

Abstract: The cerebellum plays an important role in motor learning as part of a cortico-striato-cerebellar network. Patients with cerebellar degeneration typically show impairments in different aspects of motor learning, including implicit motor sequence learning. How cerebellar dysfunction affects interactions in this cortico-striato-cerebellar network is poorly understood. The present study investigated the effect of cerebellar degeneration on activity in causal interactions between cortical and subcortical regions in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 94 publications
(126 reference statements)
13
22
0
Order By: Relevance
“…Thus, these results indicate that despite a lack of improvement in RT, some implicit sequence-specific learning was evident in all subjects. Note that using this exact same task, we have previously shown that younger healthy controls were faster during SEQ compared to RND blocks, while persons with cerebellar degeneration were not (Tzvi et al, 2017). Together with the current results, this suggests that age and neurological deficits impact on the ability to improve RT in this task.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Thus, these results indicate that despite a lack of improvement in RT, some implicit sequence-specific learning was evident in all subjects. Note that using this exact same task, we have previously shown that younger healthy controls were faster during SEQ compared to RND blocks, while persons with cerebellar degeneration were not (Tzvi et al, 2017). Together with the current results, this suggests that age and neurological deficits impact on the ability to improve RT in this task.…”
Section: Discussionsupporting
confidence: 81%
“…We also allowed an intrinsic connection between homolog M1 based on previous work (Tzvi et al, 2017). In addition, our previous fMRI studies of MSL showed that specifying the right cerebellum as input node leads to highest exceedance probability (Tzvi et al, 2017(Tzvi et al, , 2015(Tzvi et al, , 2014. We therefore chose this node as input here as well.…”
Section: Dynamic Causal Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, alterations in networks including the cerebellum have been identified, which correlate to the degrees of motor adaptation in visuomotor adaptation tasks in healthy subjects (Albert et al 2009;Della-Maggiore et al 2009). More recently, Tzvi et al (2017) found that changes in fMRI signal and functional connectivity in the cortico-striatocerebellar motor learning network were associated with learning performance in patients with cerebellar degeneration in a sequence learning task.…”
Section: Modern Brain Imaging Techniquesmentioning
confidence: 99%
“…The cerebellum has been growingly emphasized among the potential target of non-invasive neurostimulation to induce changes in cortico-cortical connectivity [32,33,34,35,36,37,38,39,40,41,42,43,44,45,46]. This is not surprising, if we take into account the growing evidence on complex and multiple connections of the cerebellum with the cerebrum to modulate cortical connectivity within the networks that are critical to orchestrate cognitive, emotional, and sensorimotor processes (including the default mode network and frontoparietal networks) [20,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47].…”
Section: Introductionmentioning
confidence: 99%